IMPLEMENTASI-BUDAYA-SEKOLAH-ADIWIYATA DI MAN-ASAHAN-KABUPATEN-ASAHAN - Izun, Tri Alfa; Mesiono, Mesiono; Marpaung, Syafri Fadillah (Hijri, 2021)
The purpose of this study was to determine: (1) Adiwiyata school culture in MAN Asahan, (2) Implementation of Adiwiyata school culture in MAN Asahan, (3) the factors that support and hinder the implementation of Adiwiyata school culture in MAN Asahan. This research uses descriptive qualitative research. The participants of this study came from MAN Asahan, namely the principal, the coordinator of the Adiwiyata team, teachers, janitors, and students. In the process of collecting data, researchers used the methods of observation, interviews, and documentation. The data analysis technique of this research uses data reduction, data presentation, data display, and verification or drawing conclusions. Meanwhile, the validity of research data was tested for credibility (internal validity), transferability (external validity), dependability (reliability), and confirmability (objectivity). The results of the study from the research can be concluded that the Adiwiyata culture carried out by MAN Asahan is by developing environmental education, maintaining the cleanliness of classrooms, buildings, gardens, ponds in the MAN Asahan environment, plant cultivation, compost management in an effort to control and overcome the environment. better. While in its implementation, the implementation of the Adiwiyata school culture itself is carried out every month and every day. In an implementation, of course, there are supporting factors and inhibiting factors. The supporting factors are the supporting Vision and Mission, supporting facilities and infrastructure, each teacher implementing an environment-based curriculum. The inhibiting factors are limited costs, lack of coordination between several related parties such as the government, hawkers, and the surrounding community. And also not yet formed the nature that is aware of the environment and responsibility. This is evidenced by the large piles of garbage in front of the madrasa whose waste comes from inside the madrasa, hawkers, and the surrounding community.Implementation of Adiwiyata School Culture, State Madrasah Aliyah